Penatalaksanaan fisioterapi pada kasus carpal Tunnel syndrome dextra Di rsud sukoharjo - Nur Siam, Ermawatir; , Dwi Rosella Komala Sari S.Fis, M.Fis (2016)
Background:Carpal Tunnel Syndrome is a common disorder with symptoms involving the median nerve. The median nerve susceptible to compression and injury in the palm of the hand and wrist, which is limited by the wrist bones (carpal) and the transverse carpal ligament. Carpal Tunnel Syndrome is caused by excessive use of the hands to repeated stress. The twist of the wrist and the use of tools that vibrate. Work that is often associated with a high incidence of Carpal Tunnel Syndrome is the process of cooking food, factory work, loading goods and construction workers. Aims of reseach:To find out the benefits of therapy Infra Red, TENS and nerve mobilization can reduce pain, increase range of motion, increase muscle strength and improve functional activity in the case of CTS dextra. Result: After treatment for 6 times the results obtained impairment silent pain: T0: 3.1 to T6: 1.6, tenderness T0: 4.8 to T6: 2.3, painful motion: T0: 6.2 to T6: 3.1, increased range of motion wrist actively dextra sagittal plane: T0: S: 60 ° -0 ° -50 ° to T6: 65 ° -0 ° -70 °, the frontal plane T0: F: 20 ° -0 ° -15 ° mnjadi T6: F: 25 ° -0 ° -20 ° and an increase in functional activity. Conclusion: Infra Red, Trancutaneus Electrical Nerve Stimulation (TENS) and Neurodynamic can reduce pain, increase range of motion, increase muscle strength and improve functional activity in the case of Carpal Tunnel Syndrome dextra.